Kikuchi-Fujimoto disease with lymph node, spleen, and liver involvement: Report of a fatal adult case with hemophagocytic lymphohistiocytosis - Corey Costantino; Peter Stenzel (Elsevier, 2016)
Kikuchi-Fujimoto disease (KFD, necrotizing lymphadenitis) is defined pathologically by enlarged lymph nodes with characteristic microscopic findings and nearly always follows a self-limiting benign clinical course. We report a case of KFD in a 47 year-old man who presented with weight loss, fever, enlarged lymph nodes and elevated serum levels of aminotransferases and bilirubin. He developed hemophagocytic lymphohistiocytosis (HLH) and died in liver failure. At autopsy, histologic findings characteristic of KFD (necrosis, histiocyte accumulation, karyorrhectic debris, absence of neutrophils) were present in lymph nodes, spleen, and liver. Similar changes were recognized upon review of a liver biopsy taken 4 weeks before death. This case demonstrates hepatic manifestations of KFD.